The Joint Declaration on the Doctrine of Justification: An Outline of its Genesis and Impact From a Baptist’s Perspective - Swarat, Uwe (Pro ecclesia, 2021)
This essay outlines the genesis and impact of the Joint Declaration on the Doctrine of Justification (JDDJ) from a Baptist perspective. Starting with comparative studies of individual theologians from 1949 to 1980 it sketches the prehistory of the JDDJ including the results of ecumenical dialogues from 1972 to 1994. The essay then presents the origins and contents of the JDDJ from the draft version (1997) to the signing (1999), including the development and content of the “Official Common Statement.” The author includes as well the impact of JDDJ on the study on “The Biblical Foundations of the Doctrine of Justification” (2012); the Notre Dame Consultation (2019); and ecumenical dialogues on justification with Baptist participation. The author appreciates the JDDJ as the most significant result of ecumenical dialogues since the formation of the ecumenical movement and expresses his hope that the Baptist World Alliance too will assent to the consensus.